2013
DOI: 10.1007/s10147-013-0563-4
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin targets the AKT–mTOR pathway for uterine leiomyosarcoma tumor growth suppression

Abstract: Curcumin inhibited uterine leiomyosarcoma tumor growth in vivo by targeting the AKT-mTOR pathway for inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Curcumin has been demonstrated to possess an antitumor effect in numerous types of cancer (9)(10)(11). Treatment with either letrozole or curcumin inhibited the xenografted endometrial tumor growth by inducing apoptosis in tumor cells, and the combination of letrozole and curcumin further strengthened the inhibitory effect on tumor growth (12).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has been demonstrated to possess an antitumor effect in numerous types of cancer (9)(10)(11). Treatment with either letrozole or curcumin inhibited the xenografted endometrial tumor growth by inducing apoptosis in tumor cells, and the combination of letrozole and curcumin further strengthened the inhibitory effect on tumor growth (12).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, derived from the herb Curcuma longa, inhibits uterine LMS cell proliferation both in vitro and in vivo experimental models through AKT-mTOR pathway [105,106], and the m-TOR inhibitor everolimus decelerates LMS growth in mice and prolongs their lifespan [107]. Temserolimus obtained PR in three of six patients with advanced LMS refractory to standard chemotherapy [108].…”
Section: Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 99%
“…Preclinical studies have identified additional pathways as potential targets in the treatment of leiomyosarcoma [64-67]. A subset of uLMS shows a loss of PTEN, resulting in aberrant signaling and increased activation of the AKT-mTOR pathway, which leads to unregulated cell proliferation.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
“…Similar to rapamycin, data from preclinical studies demonstrated that curcumin also targets the AKT-mTOR pathway and can decrease mTOR phosphorylation, as well as downstream targets, including S6 ribosomal proteins. Unlike rapamycin, curcumin also has the ability to induce apoptosis, suggesting that it may be more potent than rapamycin [66, 67]. Other authors have demonstrated the ability of curcumin to also increase autophagy and activate the ERK1/2 pathway.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%